2020
DOI: 10.3390/life10100224
|View full text |Cite
|
Sign up to set email alerts
|

Development of Postoperative Pain in Patients with End-Stage Knee Osteoarthritis Is Associated with Upregulation of Genes Related to Extracellular Matrix Degradation, Inflammation, and Apoptosis Measured in the Peripheral Blood before Knee Surgery

Abstract: Osteoarthritis (OA) pain implies an indication for joint replacement in patients with end-stage OA. However, chronic postoperative pain is observed in 10–40% of patients with OA. Here, we identified genes whose expression in the peripheral blood before surgery could denote the risk of postoperative pain development. We examined the peripheral blood of 26 healthy subjects and 50 patients with end-stage OA prior to joint replacement surgery. Pain was evaluated before surgery using the visual analog scale (VAS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Pain sensation and clinical manifestations of the OA disease were previously associated with an increase in cytokine expression [ 24 , 25 ]. Therefore, a significant decrease in SF concentrations of IL-6 and IP-10 in case of PRP treatment as well as TNFα, IL-15, Flt-3L, MIP-1β, RANTES, and VEGF in case of SVF injection in association with reduction of pain scores that were observed in our study further support this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Pain sensation and clinical manifestations of the OA disease were previously associated with an increase in cytokine expression [ 24 , 25 ]. Therefore, a significant decrease in SF concentrations of IL-6 and IP-10 in case of PRP treatment as well as TNFα, IL-15, Flt-3L, MIP-1β, RANTES, and VEGF in case of SVF injection in association with reduction of pain scores that were observed in our study further support this finding.…”
Section: Discussionmentioning
confidence: 99%
“… 46 In patients with end-stage OA, higher neuropathic-like pain scores on painDETECT and DN4 Questionnaires were found to be positively correlated with gene expression of TNF-α and IL-1β. 48 Taking these results together, there is conflicting evidence on a possible association between inflammatory cytokines and neuropathic-like pain (conclusion level 4).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported consistent significant results on blood levels of proinflammatory cytokines which were found to be correlated with presence of neuropathic-like pain, but the correlation values did not go beyond the moderate level (ie, r values ≤0.5). 48 However, the study sample included only patients with advanced knee OA and the analyses did not include potential confounders. 48 Importantly, the results of Radojčić et al revealed that the association between synovial fluid IL-6 and neuropathic-like pain was explained by synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…As OA is a multifactorial disease, the underlying pathological process is closely associated with alterations of various transcripts [ 6 , 7 , 8 , 9 , 10 ], including noncoding RNA species (ncRNAs), especially small ncRNAs, which are <200 nucleotides (nt) in length. It has been reported that unique small ncRNA expression signatures are believed not only to characterize specific types of cells, but also to be indicative of particular diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%